2016
DOI: 10.7717/peerj.2532
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomalleitype III secreted protein BipC: role in actin modulation and translocation activities required for the bacterial intracellular lifecycle

Abstract: Melioidosis, an infection caused by the facultative intracellular pathogen Burkholderia pseudomallei, has been classified as an emerging disease with the number of patients steadily increasing at an alarming rate. B. pseudomalleipossess various virulence determinants that allow them to invade the host and evade the host immune response, such as the type III secretion systems (TTSS). The products of this specialized secretion system are particularly important for the B. pseudomallei infection. Lacking in one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Here we have demonstrated that GST-BipC has the ability to bind actin directly, in the absence of other bacterial or cellular proteins. We acknowledge that whilst our study was in review, Kang et al ( 2016 ) published similar observations to those presented in our manuscript. However, upon closer inspection there is only a small amount of “overlap” with our data regarding the function of BipC as an actin binding and polymerizing factor.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Here we have demonstrated that GST-BipC has the ability to bind actin directly, in the absence of other bacterial or cellular proteins. We acknowledge that whilst our study was in review, Kang et al ( 2016 ) published similar observations to those presented in our manuscript. However, upon closer inspection there is only a small amount of “overlap” with our data regarding the function of BipC as an actin binding and polymerizing factor.…”
Section: Discussionsupporting
confidence: 85%
“…At the time of submission of this manuscript for peer review we believed this to be the first evidence that BipC is an actin-binding protein. However, we have since become aware of a similar study by Kang et al ( 2016 ), which also demonstrates that B. pseudomallei BipC is an actin-binding protein.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This study was extended to further evaluate the role of the cell invasion protein, BipC, in pathogenesis of B. pseudomallei . BipC, an immunoreactive protein, is involved in actin binding to facilitate internalization of B. pseudomallei into host cells, as a bipC mutant was impaired in adherence, invasion, and intracellular survival in epithelial cells, and BipC protein is required for full virulence in a murine model of melioidosis [ 78 , 79 ]. Recently, Vadivelu et al [ 80 ] showed that B. pseudomallei localized within the nuclear compartment of host cells, suggesting that the nucleus may play a role as an occult or transient niche for persistence of intracellular pathogens, potentially leading to recurrent episodes or recrudescence of infection.…”
Section: Molecular Pathogenesis Of B Pseudomalleimentioning
confidence: 99%
“…Internalization of B. pseudomallei can be blocked by the actin polymerization inhibitor cytochalasin D (Jones et al, 1996 ), indicating the importance of actin cytoskeletal rearrangements in the uptake of B. pseudomallei . Similarly to SipC, BipC is also able to polymerise actin in vitro and stabilizes F-actin indicating possible actin bundling activity (Kang et al, 2016a and our own unpublished observations). Interestingly, Salmonella SipA protein enhances the ability of SipC to nucleate and bundle F-actin (McGhie et al, 2001 ), but a homolog of SipA is not encoded by the genome of B. pseudomallei .…”
Section: Needle Tip and Translocator Proteins-sensing Host Contactmentioning
confidence: 80%